1983
DOI: 10.1002/jso.2930240313
|View full text |Cite
|
Sign up to set email alerts
|

Induction of colon mucosal β‐glucuronidase production as a mechanism for 1,2‐dimethylhydrazine colon carcinogenesis

Abstract: Although early studies in germ-free rats showed almost complete dependence on dimethylhydrazine (DMH) colon carcinogenesis upon the presence of colon bacteria, no adequate explanation was given for the 20% tumor incidence observed in germ-free animals. Bacterial activation of liver microsomal products releasing active proximate carcinogens has been the accepted reason for the exquisite specificity DMH has for the colon. Recent work, including the present study, show the colon mucosa is capable of metabolizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The very low jejunal bacterial population makes it likely that P-glucuronidase has originated from the mucosa of the jejunum. Studies on the enzyme activity of the various segments along the gastrointestinal tract show that P-glucuronidase activity is higher in the left colon than in the right colon and higher in the duodeno-jejunum than in the ileum but with activities in the large intestine significantly greater than in the small intestine (Celik et al 1983).…”
Section: Discussionmentioning
confidence: 98%
“…The very low jejunal bacterial population makes it likely that P-glucuronidase has originated from the mucosa of the jejunum. Studies on the enzyme activity of the various segments along the gastrointestinal tract show that P-glucuronidase activity is higher in the left colon than in the right colon and higher in the duodeno-jejunum than in the ileum but with activities in the large intestine significantly greater than in the small intestine (Celik et al 1983).…”
Section: Discussionmentioning
confidence: 98%
“…DMH, an alkylating agent, is metabolized and glucuronated by the liver, and excreted via the bile into the gut where microbial β-glucuronidase releases the active carcinogen (Celik et al 1983;Yoo et al 2001). Thus, DMH initiates tumorigenesis within the colon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mutagenic metabolites 6-hydroxy-1-acetamidopyrene (10,14,16), quercetin (2,12,18), and kaempferol (1) are released by the hydrolytic actions of BGr, BGl, and BGa on their respective glycosides. In addition, there is evidence for the presence of mucosal BGr in the intestinal tract (2,19,20) and some proof for the existence of mucosal BGa (17). However, it has been suggested that mucosal BGl exists only in the infant rat and disappears by the third week of life (9).…”
mentioning
confidence: 99%